Elastic bands in combination with free weights in strength training: Neuromuscular effects - Andersen, V.; Fimland, M. S.; Kolnes, M. K.; Saeterbakken, A. H. (The Journal of Strength and Conditioning Research, 2015)
This study compared the effects of a variable vs. a constant lower limb resistance training program on muscle strength, muscle activation, and ballistic muscle performance at different knee angles. Thirty-two females were randomized to a constant resistance training free-weight group (FWG) or a variable resistance training group using free weights in combination with elastic bands (EBG). Two variations of the squat exercise (back squat and split) were performed 2 days per week for 10 weeks. Knee extensor maximal voluntary isometric contraction (MVC) and countermovement jump were assessed at knee angles of 60, 90, and 120° before and after the intervention. During the MVCs, muscle activation of the superficial knee extensor muscles was measured using surface electromyography. The FWG increased their MVCs at 60 and 90° (24 and 15%, respectively), whereas the EBG only increased significantly at 60° (15%). The FWG increased their jump height significantly at all angles (12-16%), whereas the EBG only improved significantly at 60 and 90° (15 and 10%, respectively). Both groups improved their 6-repetition maximum free-weight squat performance (EBG: 25% and FWG: 23%). There were no significant changes in muscle activation. In conclusion, constant and variable resistance training provided similar increases in dynamic and isometric strength, and ballistic muscle performance, albeit most consistently for the group training only with free weights.